Ion‐Pair Interactions in Polyphenylene‐Based Quaternized Membranes Designed for Phosphoric Acid‐Doped Proton Exchange Membranes for High‐Temperature Fuel Cells - Guo, Lin; Miyatake, Kenji; Mahmoud, Ahmed Mohamed Ahmed; Liu, Fanghua; Xian, Fang; Yadav, Vikrant; Hao, Xiaofeng; Wang, Shuanjin; Meng, Yuezhong (Advanced science, 2025)
Phosphoric acid (PA)‐doped proton exchange membranes (PEMs) face significant challenges owing to the loss of PA, particularly under high humidity conditions. Ion‐pair interactions between PA and quaternary ammonium (QA) groups can effectively mitigate PA loss. Herein, polyphenylene‐based quaternized membranes (BAF‐QAF and C7‐QAF) comprising distinct hydrophobic moieties [BAF = (perfluoropropane‐2,2‐diyl)dibenzene and C7 = 1,1‐diphenylcycloheptane] and fluorenyl groups with pendant QA head groups are designed and used as PA‐doped PEMs with low or no fluorine contents to realize high‐temperature and low‐humidity operability. The resulting membranes exhibited excellent PA retention, maintaining >85% of their initial proton conductivities at 90% relative humidity after 10 humidity cycles. PA‐doped membranes PA‐C7‐QAF and PA‐BAF‐QAF exhibit superior proton conductivities of 60.3 and 58.4 mS cm −1 at 160 °C, respectively. PA‐C7‐QAF and PA‐BAF‐QAF fuel cells deliver peak power densities of 0.579 and 0.537 W cm −2 at 140 °C and 0.706 and 0.640 W cm −2 at 160 °C, respectively, under dehumidified conditions. The PA‐C7‐QAF cell also exhibits impressive durability with an average voltage decay of 30 µV h −1 (140 °C, 0.15 A cm −2 ) after an initial voltage drop. These findings underscore PA‐C7‐QAF and PA‐BAF‐QAF membranes as promising components in high‐temperature fuel cells.